Lymphomas in cartilage-hair hypoplasia – A case series of 16 patients reveals advanced stage DLBCL as the most common form - Kukkola, Hanna-Leena; Utriainen, Pauliina; Huttunen, Pasi; Taskinen, Mervi; Mäkitie, Outi; Vakkilainen, Svetlana (Frontiers in Immunology, 2022)
Background: Patients with cartilage-hair hypoplasia (CHH) have an increased risk of malignancy, particularly non-Hodgkin lymphoma and basal cell carcinoma. The characteristics, clinical course, response to therapy and outcome of lymphomas in CHH remains unexplored. Methods: We assessed clinical features of lymphoma cases among Finnish patients with CHH. Data were collected from the Finnish Cancer Registry, hospital records, the National Medical Databases and Cause-of-Death Registry of Statistics Finland. Results: Among the 160 CHH patients, 16 (6 men, 10 women) were diagnosed with lymphoma during 1953-2016. Lymphoma was diagnosed in young adulthood (median age 26.4 years, range from 6.4 to 69.5 years), mostly in advanced stage. The most common lymphoma type was diffuse large cell B-cell lymphoma (DLBCL) (6/16, 38%). Eight patients received chemotherapy (8/16, 50%), and two of them survived. Standard lymphoma chemotherapy regimens were administered in the majority of cases. Altogether, eleven CHH patients died due to lymphomas (11/16, 69%). In almost all surviving lymphoma patients, the diagnosis was made either during routine follow-up or after evaluation for non-specific mild symptoms. Search for CHH-related clinical predictors demonstrated higher prevalence of recurrent respiratory infections, in particular otitis media, and Hirschsprung disease in patients with lymphoma. However, three patients had no clinical signs of immunodeficiency prior to lymphoma diagnosis. Conclusion: DLBCL is the most common type of lymphoma in CHH. The outcome is poor probably due to advanced stage of lymphoma at the time of diagnosis. Other CHH-related manifestations poorly predicted lymphoma development, implying that all CHH patients should be regularly screened for malignancy.